1990
DOI: 10.1111/j.1559-1816.1990.tb00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy Accessibility and the Influence of Outcome Expectancies on Adolescent Smokeless Tobacco Use

Abstract: This study investigated the moderating influence of expectancy accessibility on the relation between outcome expectancies and drug use intentions. Specifically, it was hypothesized that expectancies made temporarily more accessible would predict smokeless tobacco intentions to a greater degree than would less accessible expectancies. In addition, it was anticipated that expectancies regarding positive outcomes of smokeless tobacco use would be better predictors of intention than would expectancies about negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 36 publications
4
58
1
Order By: Relevance
“…Positive expectancies are typically more strongly related to alcohol use than are negative expectancies (Brown, Creamer, and Stetson, 1987;Collins, Lapp, Emmons, and Isaac, 1990;Fromme, Stroot, and Kaplan, 1993;Southwick, Steele, Marlatt, and Lindell, 1981;Stacy et al, 1990a), although negative expectancies might prove important in the prediction of abstinence and efforts to resist drinking (Jones and McMahon, 1996;Leigh and Stacy, 2004).…”
Section: The Role Of Expectancy In Drug Usementioning
confidence: 94%
“…Positive expectancies are typically more strongly related to alcohol use than are negative expectancies (Brown, Creamer, and Stetson, 1987;Collins, Lapp, Emmons, and Isaac, 1990;Fromme, Stroot, and Kaplan, 1993;Southwick, Steele, Marlatt, and Lindell, 1981;Stacy et al, 1990a), although negative expectancies might prove important in the prediction of abstinence and efforts to resist drinking (Jones and McMahon, 1996;Leigh and Stacy, 2004).…”
Section: The Role Of Expectancy In Drug Usementioning
confidence: 94%
“…In addition, the predictive superiority of positive expectancies over negative expectancies and attitude suggested that models that focus primarily on health beliefs referring to negative outcomes of a behavior are likely to be incomplete explanations of health behavior. Other research also has found support for the distinction between positive and negative expectancies (Christiansen, Goldman, & Inn, 1982;Rohsenow, 1983;Stacy, Dent, et al, 1990).…”
Section: General Expectancy Dimensions and Attitudementioning
confidence: 94%
“…For example, Rather, Goldman, Roehrich, and Brannick (1992) found evidence that outcome expectancies regarding alcohol use can be modeled as a network of relationships in memory. Also, Stacy, Dent, et al (1990) found that a manipulation of the accessibility of positive outcomes of tobacco use from memory moderated the predictive effects of outcome expectancies on behavior intentions toward tobacco use.…”
mentioning
confidence: 96%
“…Most research derived from this framework has been closely aligned with work on outcome expectancies (e.g., Goldman et al, 1991;Stacy, Dent, et al, 1990), operationally defined as behavioral beliefs (Ajzen & Fishbein, 1980) or subjective probabilities of outcomes (Bauman, 1980) as reported on questionnaires. In this literature, outcome expectancies have been shown to be strongly related to drug use, and this relationship has been described recently as a memory process.…”
mentioning
confidence: 99%